Biochar co‐compost improves nitrogen retention and reduces carbon emissions in a winter wheat cropping system. Issue 4 (25th January 2023) - Gao, Si; Harrison, Brendan P.; Thao, Touyee; Gonzales, Melinda L.; An, Di; Ghezzehei, Teamrat A.; Diaz, Gerardo; Ryals, Rebecca A.
Abstract: Organic amendments, such as compost and biochar, mitigate the environmental burdens associated with wasting organic resources and close nutrient loops by capturing, transforming, and resupplying nutrients to soils. While compost or biochar application to soil can enhance an agroecosystem's capacity to store carbon and produce food, there have been few field studies investigating the agroecological impacts of amending soil with biochar co‐compost, produced through the composting of nitrogen‐rich organic material, such as manure, with carbon‐rich biochar. Here, we examine the impact of biochar co‐compost on soil properties and processes by conducting a field study in which we compare the environmental and agronomic impacts associated with the amendment of either dairy manure co‐composted with biochar, dairy manure compost, or biochar to soils in a winter wheat cropping system. Organic amendments were applied at equivalent C rates (8 Mg C ha −1 ). We found that all three treatments significantly increased soil water holding capacity and total plant biomass relative to the no‐amendment control. Soils amended with biochar or biochar co‐compost resulted in significantly less greenhouse gas emissions than the compost or control soils. Biochar co‐compost also resulted in a significant reduction in nutrient leaching relative to the application of biochar alone or compost alone. Our results suggest that biochar co‐composting could optimize organic resource recycling for climate change mitigation and agricultural productivity while minimizing nutrient losses from agroecosystems. Abstract : Organic soil amendments such as biochar and compost can improve soil health and reduce the environmental impacts of agriculture. However, few field studies have examined the potential of biochar co‐compost, produced by composting organic materials together with biochar. In a field study, we compare the performance of biochar, compost, and biochar co‐compost when applied to soils in a winter wheat cropping system. We found that the biochar co‐compost had both environmental and agronomic advantages over both biochar and compost, suggesting that biochar co‐composting could optimize the beneficial reuse of organic materials for agricultural purposes.